2015
DOI: 10.1097/scs.0000000000001081
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Ptosis in a Patient With Blepharochalasis

Abstract: A 37-year-old woman presented with right upper eyelid blepharochalasis with ptosis. Right upper eyelid edema had occurred 2 to 3 times per year by 30 years old, although the frequency decreased with age. The edema occurred spontaneously and resolved within 1 to 2 days. She underwent a right levator tucking surgery at 22 years old, and the ptosis recurred 2 years postoperatively. She again underwent ptosis surgery with skin excision at 37 years old. The intraoperative findings showed a thin levator aponeurosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…However, palpebral ptosis recurred after 3 months, suggesting the need for further surgery. Huemer et al and Takahashi et al reported similar cases of recurrence after surgery [14,15]. Although the immediate postoperative result was satisfactory, their patients also required a second operation.…”
Section: Discussionmentioning
confidence: 88%
“…However, palpebral ptosis recurred after 3 months, suggesting the need for further surgery. Huemer et al and Takahashi et al reported similar cases of recurrence after surgery [14,15]. Although the immediate postoperative result was satisfactory, their patients also required a second operation.…”
Section: Discussionmentioning
confidence: 88%
“…Ptosis (48.39%) was the most common manifestation among these cases. Some scholars hypothesized that the probable site of the lesion was in the aponeurosis or its insertion [ 13 ], which required further histopathological support. The second common manifestation was the lacrimal gland prolapse (44.09%), which was occurred due to the atrophic changes of the orbital septum.1 As for the deformity of the lateral or inner canthal angle, the dehiscence of attachments of upper and lower eyelids to the lateral position and occasionally medial canthal tendons were considered as the main causative reasons [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ptosis (48.39%) was the most common manifestation among these cases. Some scholars hypothesized that the probable site of the lesion was in the aponeurosis or its insertion [14], which required further histopathological support. The second common manifestation was the lacrimal gland prolapse (44.09%), which was occurred due to the atrophic changes of the orbital septum.1 As for the deformity of the lateral or inner canthal angle, the dehiscence of attachments of upper and lower eyelids to the lateral position and occasionally medial canthal tendons were considered as the main causative reasons [15].…”
Section: Discussionmentioning
confidence: 99%